HUBUNGAN STATUS GIZI STUNTING PADA BALITA DENGAN KEJADIAN TUBERKULOSIS - Nyimas Nafllah Nadila (Yayasan Pendidikan Medika Indonesia, 2021)
Background: Tuberculosis or commonly called TBC is a chronic disease that affects almost all organs of the body, which is found in the lungs. This disease is mostly found in densely populated environments. Based on the Tuberculosis Prevalence Survey in 2013-2014, the incidence of TB with bacteriological confirmation in Indonesia was 759 per 100,000 population aged 15 years and over and the incidence of TB with smear positive was 257 per 100,000 population aged 15 years and over. Methods: The method used is the method of studying literature from various national and international journals as well. This method searches for and combines the contents of various journals and analyzes facts from valid research sources. Results: The children under five with stunting nutritional status had a 2.96 times risk of suffering from TB disease than toddlers with normal nutritional status and toddlers with severe stunted nutritional status had 8.18 times risk of developing TB disease. Toddlers with severe stunting nutritional status are at a higher risk than normal nutritional infants. Conclusion: Nutritional status suggests an important role as a child growth process, poor nutritional status and even stunting have a negative impact on children's growth, one of which is a child who has a weak immune system which causes children to be susceptible to infectious diseases, stunting nutritional status has risks. which is high for children who are sick with TB.